Evolution of Linoleic Acid Biosynthesis Paved the Way for Ecological Success of Termites - Macháček, Stanislav; Tupec, Michal; Horáček, Natan; Halmová, Martina; Roy, Amit; Machara, Aleš; Kyjaková, Pavlína; Lukšan, Ondřej; Pichová, Iva; Hanus, Robert (Molecular biology and evolution, 2023)
Termites are dominant animals of tropical terrestrial ecosystems. Their success is due to their eusocial organization as well as their ability to digest dead plant tissues. While being extremely abundant, the termite diet is poor in crucial nutrients, such as fatty acids. Linoleic acid (LA) is a precursor for many vital biomolecules, and most animals depend on its dietary supply. Termites count among the exceptions known to produce LA de novo, presumably via the action of an unknown Δ12 fatty acyl desaturase (FAD) introducing the second double bond into monounsaturated oleic acid. Here, we search for the evolutionary origin of LA biosynthesis in termites. To this end, we compile the repertoire of FAD homologs from 57 species of termites and their closest relatives, the cockroaches, analyze FAD phylogeny, and identify a potential Δ12 FAD branch, which arose through duplication of a likely Δ9 FAD. We functionally characterize both paralogs and identify the Δ9 activity in the ancestral FAD-A1a and the Δ12 activity responsible for LA biosynthesis in FAD-A1b. Through the combination of homology modeling and site-directed mutagenesis, we pinpoint structural features possibly contributing to the distinct functions, regiospecificities, and substrate preferences of the two enzymes. We confirm the presence of both paralogs in all 36 studied species of the Blattoidea lineage (Blattidae, Lamproblattidae, Cryptocercidae, and termites) and conclude that we identified an evolutionary event important for the ecological success of termites, which took place in their cockroach ancestors roughly 160 My and remained conserved throughout termite diversification into 3,000 extant species.
Keywords: Isoptera; mastné kyseliny; Phylogeny; termites; ekosystém; švábi; biosynthesis; fatty acyl desaturases; Animals; kyselina linolová; Blattodea; Fatty Acids; Ecosystem; linoleic acid; zvířata; fylogeneze; Cockroaches; Linoleic Acid